The Impact of the Management of Angsana Beach Tourist Attractions in Angsana District, Tanah Bumbu Regency on Economic, Social and Cultural as well as the Environment - Defvy Ayuningtyas; Mutiani Mutiani; M. Ridha Ilhami; Syarifuddin Syarifuddin; Fatwa Nur'aini (Journal of Social Development, 2026)
The impact of the management of the Angsana Beach tourist attraction in Angsana District, Tanah Bumbu Regency, on the economy, social, culture, and environment can be seen from increasing community income, strengthening social interactions, preserving local culture, and sustainable environmental conservation efforts. This study aims to analyze the impact of the management of Angsana Beach tourist attractions in Angsana District, Tanah Bumbu Regency on the economy, social and culture as well as the environment. The research method used is a qualitative approach by utilizing primary and secondary data, as well as analytical techniques including data reduction, data presentation, and validation through triangulation. The results of this study show that the impact of the management of Angsana Beach tourist attractions in Angsana District, Tanah Bumbu Regency, shows a significant increase in the economic, social, and cultural aspects of the community, as well as sustainable environmental conservation efforts through cooperation between various stakeholders. The positive results of the Angsana Beach tourist attraction management in Angsana District, Tanah Bumbu Regency, resulted in an improvement in the community's economy, stronger social interaction between tourists and local residents, and sustainable environmental preservation through collaboration in resource management. These findings also contribute academically and practically, including as a reference source for social studies lessons at the junior high school level on economic potential and community empowerment.